Pengaruh Persepsi Siswa Tentang Keterampilan Dasar Mengajar Guru terhadap Hasil Belajar Matematika - Rizaldi Muharmansyah; M. Imamuddin; Ulva Rahmi; Tasnim Rahmat (Journal on Education, 2023)
This research is a quantitative study using the ex post facto method, with a total population of 89 students of class X MAN 4 AGAM and a sample of 49 students taken by a proposive sampling. Data on students' perceptions of teachers' teaching skills were obtained from distributing questionnaires to students while data on student learning outcomes was obtained from documentation. The data analysis method used is simple linear regression analysis with an error rate of 5%. Based on the data analysis that has been carried out, the results obtained are the magnitude of the correlation coefficient of 0.653 which is in the strong relationship category. Meanwhile, the contribution made by the variable of student perceptions about the teacher's teaching skills to the variable of student learning outcomes is 43% while the rest is influenced by other factors. From calculations using the regression formula, the regression equation Y = -109.81 + 2.793245x is obtained. Based on the results of the hypothesis test, Tcount>Ttable was obtained, namely 7.88> 1.678 with a significance level of 5%. Based on the results of the consultation of these values, the formulated hypothesis can be accepted, meaning that there is a significant influence between students' perceptions of the teacher's teaching skills on the mathematics learning outcomes of class X MAN 4 AGAM.